1993
DOI: 10.1002/ijc.2910540513
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and characterization of human ocular melanoma cell lines

Abstract: Five continuous cell lines have been established from 29 ocular melanomas and maintained for periods ranging from 3 to 9 years in medium identical to that in which 3 concomitantly studied lines of cutaneous melanoma cells were cultured as controls. The long-term problems to be overcome in establishing uveal cell lines are related to cell-doubling times which ranged from 72 to 432 hr, and plating efficiency, which ranged from 0.5%-6.5%. Tumors and cell lines were found to contain melanosomes. The morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
17
0
Order By: Relevance
“…Despite the difficulties in culturing human UM cells, we achieved a success rate similar to that described by other authors [Aubert et al, 1993]. We found that primary cell cultures derived from UM have a slow growing rate and need between 6 and 10 days to double their number.…”
Section: Discussion Um Primary Cell Cultures and Cell Cyclesupporting
confidence: 82%
“…Despite the difficulties in culturing human UM cells, we achieved a success rate similar to that described by other authors [Aubert et al, 1993]. We found that primary cell cultures derived from UM have a slow growing rate and need between 6 and 10 days to double their number.…”
Section: Discussion Um Primary Cell Cultures and Cell Cyclesupporting
confidence: 82%
“…The melanoma cell lines JPC 298 (Aubert et al, 1993), A375 (Giard et al, 1973), Mewo (Bean, 1975), P1 (kindly provided by Dr Dummer, Zurich), SK-Mel28 (Carey et al, 1976), HT144 (Ahrens et al, 2001), Bro (Lockshin et al, 1985) were maintained in RPMI 1640 with stable glutamine supplemented with penicillin (400 U/ml), streptomycin (50 mg/ml), ascorbic acid (50 mg/ml) and 10% fetal calf serum (Seromed s , Biochrom KG; Berlin, Germany), in a humidified atmosphere of 5% CO 2 at 371C.…”
Section: Cell Lines and Culture Conditionsmentioning
confidence: 99%
“…In contrast to short-term cultivation, performing studies by using cell lines has the advantage of stable and reproducible experimental conditions caused by regular growth patterns of the cells. For this reason, several attempts for the establishment of cell lines derived from primary uveal melanomas were made in the past [4,5,6,7,8]. Compared to other malignancies, uveal melanomas are rare and difficult to cultivate.…”
Section: Introductionmentioning
confidence: 99%